CA 19-9 levels in patients with acute pancreatitis due to gallstone and metabolic/toxic reasons - Binicier,Omer Burcak (2019)
SUMMARY OBJECTIVE Acute pancreatitis (AP) is an important clinical event with an increased frequency due to increased life expectancy, obesity, and alcohol use. There are some data about the elevation of carbohydrate antigen (CA) 19-9 levels in benign and malignant pancreaticobiliary events in the literature, but in AP they are limited. The aim of this study was to evaluate the CA 19-9 level in patients with AP and determine its relationship according to the cause. METHODS Between 2010-2018, 173 patients evaluated with CA 19-9 levels as well as by standard laboratory tests were included in the study. CA 1 9-9 levels and laboratory findings were compared in patients with pancreatitis due to gallstone (group 1) and metabolic/toxic reasons such as hyperlipidemia, alcohol, or drug use (group 2). RESULTS There were 114 (66%) patients in the group 1 and 59 (34%) patients in the group 2. The majority of patients with high CA 19-9 level were in group 1 (92.1% vs 6.8%). CA 19-9 level, as well as amylase, lipase, AST, ALT and bilirubin levels were found to be statistically higher in patients with AP due to gallstone compared to patients with metabolic/toxic AP. CONCLUSIONS Patients with AP due to gallstone, were found to have a high level of CA 19-9 at admission. Early stage CA 19-9 levels may contribute to standard laboratory tests in the etiology of the disease in patients diagnosed with AP.